2013
DOI: 10.1109/jphotov.2013.2262374
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Spacer and Catalytic Layers in Monolithic Dye-Sensitized Solar Cells

Abstract: Over the past few years, dye-sensitized solar cell (DSC) research has been focused on the material and process cost\ud reduction, and on the electronics integration of the devices.Monolithic design is one of the most promising DSC architectures for\ud mass production, because it allows the elimination of one conductive substrate and offers the possibility of printing layer-by-layer\ud the materials that compose the structure. In this study, the formulation, the realization, and the processing of the spacer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…The thickness of the carbon layer as the optimum counter electrode in the range 60-70 μm (to obtain low resistance) [9]. The thickness of the resulting carbon paste herein is thinner than the optimum thickness.…”
Section: IIImentioning
confidence: 97%
See 1 more Smart Citation
“…The thickness of the carbon layer as the optimum counter electrode in the range 60-70 μm (to obtain low resistance) [9]. The thickness of the resulting carbon paste herein is thinner than the optimum thickness.…”
Section: IIImentioning
confidence: 97%
“…Therefore, the I-V characteristics and solar cell efficiency can be improved [9]. Table 2 shows that the lowest sheet resistance value was obtained by the carbon paste that uses activated carbon compared to the resulting sheet resistance value of carbon paste using carbon nanopowder are 10.70 Ω/sq and 11.09 Ω/sq.…”
Section: Measured Using Nitrogen Gas Sorption Techniquementioning
confidence: 99%
“…The carbon paste was prepared according to a recipe published elsewhere [10], i.e. carbon black (150 mg) was mixed thoroughly with graphite (210 mg), P25 (310 mg), acetic acid (0.15 mL), and deionized water (2 mL) in a mortar.…”
Section: B Cell Fabricationmentioning
confidence: 99%
“…The challenges that arise from such scheme is typically related to the spacer and counter-electrode material. Previous study showed that the thickness of both spacer and counter-electrode materials have significant effects on the performance of monolithic DSSC [10]. The type of catalytic material on the counter-electrode, however, has not been specifically discussed.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of efficient dyes and electrodes with high catalytic activity, the certified efficiency of DSC has reached 11.9% with an active area of 1.005 cm 2 , . Recently, improving the module performance has gained increasing attention .…”
Section: Introductionmentioning
confidence: 99%